ANALISIS KOMUNIKASI GURU MATA PELAJARAN DALAM MENJALANKAN PERAN BIMBINGAN KONSELING - Syisva Nurwita (Professional: Jurnal Komunikasi dan Administrasi Publik, 2015)
Counseling activities should be performed by counseling teacher that has been trained and educated in the field. In fact, studies teachers who also acted as a tutor didn’t understand the concept of tutor commonly called counselor, because of their educational background were not Guidance and Counseling Study Program. In the course of counseling, teachers needed to understand the elements of respect, empathy, audible, clarity and humble in running the guidance. Writer wanted to know the effectiveness of communication run by Subject teachers in performing the role of a counselor. This is a qualitative research. Data was collected by using observation, interviews and documentation techniques. The results showed that: (1) the understanding between teachers and students has been established as Civic Education teachers attempted to understand the counseling activities, (2) there’s a sense of fun between Civic Education teachers and students when they are running the counseling, (3) a change in attitude after the counseling on students, (4) good social relations, (5) after the communication, students can change the attitude or act according to the direction of Civic Education teachers who acts as a Counselor.Keywords: Communication, Guidance, Counseling